Associations between gut microbiota and sleep: a two-sample, bidirectional Mendelian randomization study - Wu, Jun; Zhang, Baofu; Zhou, Shengjie; Huang, Ziyi; Xu, Yindong; Lu, Xinwu; Zheng, Xiangtao; Ouyang, Dong (Frontiers in Microbiology, 2023)
Previous research has reported that the gut microbiota performs an essential role in sleep through the microbiome-gut-brain axis. However, the causal association between gut microbiota and sleep remains undetermined. We performed a two-sample, bidirectional Mendelian randomization (MR) analysis using genome-wide association study summary data of gut microbiota and self-reported sleep traits from the MiBioGen consortium and UK Biobank to investigate causal relationships between 119 bacterial genera and seven sleep-associated traits. We calculated effect estimates by using the inverse-variance weighted (as the main method), maximum likelihood, simple model, weighted model, weighted median, and MR-Egger methods, whereas heterogeneity and pleiotropy were detected and measured by the MR pleiotropy residual sum and outlier method, Cochran's Q statistics, and MR-Egger regression. In forward MR analysis, inverse-variance weighted estimates concluded that the genetic forecasts of relative abundance of 42 bacterial genera had causal effects on sleep-associated traits. In the reverse MR analysis, sleep-associated traits had a causal effect on 39 bacterial genera, 13 of which overlapped with the bacterial genera in the forward MR analysis. In conclusion, our research indicates that gut microbiota may be involved in the regulation of sleep, and conversely, changes in sleep-associated traits may also alter the abundance of gut microbiota. These findings suggest an underlying reciprocal causal association between gut microbiota and sleep.